The Impact of Lived-Experience Based Therapy and Cognitive-Behavior Therapy on Body Mass Index and Self-Esteem among Obese Women - Babadi, Alireza; Bagher Kajbaf, Mohammad; Nouri, Abolghasem; Abedi, Mohammad Reza (International Journal of Applied Behavioral Sciences, 2019)
Introduction: Culturally sensitive psychological intervention among individuals with obesity has gained major attention among experts in psychological fields. The current study was to examine and compare the impact of the Lived–Experienced Based Therapy (LEBT) and Cognitive-Behavioral Therapy (CBT) on BMI and self-esteem among Iranian obese women in Esfahan City, Iran. Method: The study used quasi-experimental method with pre-test, post-test and 3-month follow-up. The study population consisted of all females with BMI above 30, in Esfahan. Overall, 45 women (M= 34.11, SD= 5.60) were purposefully selected and randomly divided into three study groups. The sample was selected using online and display ads. Both treatment groups received 8 sessions of specific interventions from April to June 2018, while the control group did not receive any therapies. Data were collected using the global formula calculating BMI and Rosenberg Self-Esteem Scale (1965) and analyzed by SPSS-21 software. The ANCOVA and repeated measure ANOVA (i.e., Bonferroni test analysis) were used to compare three groups at three stages of pre-test, post-test and follow-up. Results: The results showed that BMI and self-esteem in both experiment groups were significantly improved at both post-test and follow-up, compared to the pre-test and control group (p<.001). However, there was no significant difference between the effectiveness of CBT and LEBT in both stages of post-test and follow-up. Conclusion: Both psychological therapies are effective to address low self-esteem and high BMI of obese women. Declaration of Interest: None